Poetic Discourse In The Poetry Of Azam Oktam And Minhojiddin Mirzo - Butunboeva Tumaris A’zamjonovna (Zien Journals, 2021)
The poetical discourse has a specific cadenced tune. It is through this all-encompassing tone and symbolism that the craftsman communicates the sentiments, internal encounters, contemplations, psycho-social perspectives on his expressive hero, that is, the aesthetic data that the artist's "I" needs to pass on to the audience (per user). In the article, there is given T.E.Lessing, S.Saporta, B.Larin, E.Koseriu, G.O.Vinokur, L.V.shcherba, V.M.Jirmunskiy, A.A.Potebnya, M.M.Bakhtin, the examination of M P.Brandes, M.I.Kojina and numerous different researchers express their perspectives on the investigation of Linguo-poetics as a different science, just as the examination of the otherworldly and tasteful highlights of the sonnets of the People's Poets of Uzbekistan Azam Uktam and Minhojiddin Mirzo.
Keywords: Workmanship; beautiful talk; Lingvo poetics; degree; Lingvo pragmatics; word craftsmanship; mindfulness